Gender mismatch between donor and recipient is a factor of morbidity but does not condition survival after cardiac transplantation. (29th September 2014) - Correia, Pedro; Prieto, David; Batista, Manuel; Antunes, Manuel J.
Summary We intended to evaluate the influence of sex mismatch between donor and recipient, which is still under much debate, on survival and comorbidities after cardiac transplantation. From November 2003 to December 2013, a total of 258 patients were transplanted in our center. From these, 200 receptors were male (77.5%) and constituted our study population, further divided into those who received the heart from a female donor (Group A) – 44 patients (22%) and those who received it from a male donor (Group B) – 156 (78%). Median follow‐up was 4.2 ± 3.0 years (1–10 years). The two groups were quite comparable with each other, except for body mass index, systolic pulmonary artery pressure, and transpulmonary gradient, which were significantly lower in Group A. A low donor/recipient weigh ratio (<0.8) was avoided whenever possible. Hospital mortality was not different in the two groups. During follow‐up, global survival was similar, as was survival free from acute cellular rejection and cardiac allograft vasculopathy. However, patients in Group A had decreased survival free from serious infections and malignant tumors. Allocation of female donors to male receptors can be done safely, at least in receptors without pulmonary hypertension and when an adequate donor/recipient weigh ratio is ensured.